The 50th Anniversary of the Committee on Acoustics of the Polish Academy of Sciences - RAKOWSKI, Andrzej; ŚLIWINSKI, Antoni (Archives of Acoustics, 2014)
The Committee on Acoustics of the Polish Academy of Sciences was founded in 1964 by the reso lution of the General Assembly of the Polish Academy of Sciences, within its Division of Engineering Sci ences (Division 4). The idea of creating the Committee was brought up by Professor Ignacy Malecki, a distinguished scientist, an academic teacher, and an internationally acclaimed authority on acoustics.